Enrichment of a continuous culture of Saccharomyces cerevisiae with the yeast Issatchenkia orientalis in the production of ethanol at increasing temperatures - Gallardo, J. C. M. [UNESP]; Souza, C. S.; Cicarelli, Regina Maria Barreto [UNESP]; Oliveira, K. F. [UNESP]; Morais, M. R. [UNESP]; Laluce, Cecília [UNESP] (Springer Heidelberg, 2011)
A fermentation system was continuously fed with sugar-cane syrup and operated with recycling of Saccharomyces cerevisiae cells at temperatures varying from 30 to 47A degrees C. The aim of the present work was to obtain and study the colonies of isolates showing elongated cells of yeasts which were sporadically observed at the end of this continuous process. Based on a sequence of assays involving methods of classical taxonomy and RAPD-PCR, two groups of isolates showing characteristics of non-Saccharomyces yeasts were identified in the yeast population where S. cerevisiae was the dominant yeast. The largest group of non-Saccharomyces yeasts, resulting from a slow proliferation over the 2 months, reached a final level of 29.6% at the end of the process. RAPD-PCR profiles obtained for the isolates of this dominant non-Saccharomyces yeast indicated that they were isolates of Issatchenkia orientalis. Pichia membranifaciens was the only species of non-Saccharomyces yeast detected together with I. orientalis but at a very low frequency. The optimum temperature for ethanol formation shown by the isolate 195B of I. orientalis was 42A degrees C. This strain also showed a faster ethanol formation and biomass accumulation than the thermotolerant strain of S. cerevisiae used as the starter of this fermentation process. Some isolates of I. orientalis were also able to grow better at 40A degrees C than at 30A degrees C on plates containing glycerol as carbon source. Yeasts able to grow and produce ethanol at high temperatures can extend the fermentation process beyond the temperature limits tolerated by S. cerevisiae.
Keywords: Saccharomyces cerevisiae; Issatchenkia orientalis; Pichia membranifaciens; Fermentation at high temperatures; Ethanol production